Alpha-1 Antitrypsin Inhibits ATP-Mediated Release of Interleukin-1β via CD36 and Nicotinic Acetylcholine Receptors - Siebers, Kathrin; Fink, Bijan; Zakrzewicz, Anna; Agné, Alisa; Richter, Katrin; Konzok, Sebastian; Hecker, Andreas; Zukunft, Sven; Küllmar, Mira; Klein, Jochen; McIntosh, J. Michael; Timm, Thomas; et al. (Frontiers in Immunology, 2018)
While interleukin (IL)-1β is a potent pro-inflammatory cytokine involved in host defense, high levels can cause life-threatening sterile inflammation including systemic inflammatory response syndrome. Hence, the control of IL-1β secretion is of outstanding biomedical importance. In response to a first inflammatory stimulus such as lipopolysaccharide, pro-IL-1β is synthesized as a cytoplasmic inactive pro-form. Extracellular ATP originating from injured cells is a prototypical second signal for inflammasome-dependent maturation and release of IL-1β. The human anti-protease alpha-1 antitrypsin and IL-1β regulate each other via mechanisms that are only partially understood. Here, we demonstrate that physiological concentrations of alpha-1 antitrypsin efficiently inhibit ATP-induced release of IL-1β from primary human blood mononuclear cells, monocytic U937 cells and rat lung tissue, whereas ATP-independent IL-1β release is not impaired. Both, native and oxidized alpha-1 antitrypsin are active, suggesting that the inhibition of IL-1β release is independent of the anti-elastase activity of alpha-1 antitrypsin. Signaling of alpha-1 antitrypsin in monocytic cells involves the lipid scavenger receptor CD36, calcium-independent phospholipase A2β and the release of a small soluble mediator. This mediator leads to the activation of nicotinic acetylcholine receptors, which efficiently inhibit ATP-induced P2X7 receptor activation and inflammasome assembly. We suggest that alpha-1 antitrypsin controls ATP-induced IL-1β release from human mononuclear blood cells by a novel triple-membrane-passing signaling pathway. This pathway may have clinical implications for the prevention of sterile pulmonary and systemic inflammation.